PENGARUH RELIGIUSITAS DAN ETIKA KERJA ISLAMI TERHADAP ETOSKERJA PEDAGANG MUSLIM (Studi Kasus Pasar Besar Kota Malang) - Wijaya, Ardhimas Indra; Pardiman, Pardiman; Harijanto, Djony (Universitas Al-Amien Prenduan, 2022)
The population in Indonesia has a variety of ethnicities and different tribes. Some races and tribes greatly influence economic, social, and cultural diversity.Â Â The existence of other nationalities will cause different mentalities so that the work ethic that each individual or group has will also be different. Several factors influence the work ethic, one of which is religiosity and Islamic work ethics. This article aims to analyze the effect of religiosity and Islamic work ethics on the work ethic of Muslim traders. The study's results stated that state financial managers who want the creation of religiosity variables have a positive and insignificant effect on work ethic. Meanwhile, Islamic work ethic variables have a positive and significant impact on the work ethic of Muslim traders.